PENGARUH METODE GAME BASED LEARNING (GBL) TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN FIQIH KELAS VIII MTs. MUHAMMADIYAH 12 PALIRANGAN TAHUN PELAJARAN 2023/2024 - Zakiyyatul Husaini dan Himmatul Husniyah (Jurnal Mahasiswa Pendidikan, 2024)
Abstract: The use of learning methods is one of the methods used by teacher in conveying lesson material to students during the learning process in an effort to improve student learning outcomes. One of the methods that can be used in learning PAI is Fiqh lessons, namely the game based learning (GBL) method, using certain game methods or games as a learning tool. The aim of this research is to find out how the method is implemented and whether there is an influence of the game based learning (GBL) method on the learning outcomes of students in the Fiqh subject at junior high school 12 in Palirangan 2023/2024 academic year.To achieve this goal, this research uses a quantitative type of research using a parametric statistical analysis approach and using correlational analysis methods. The data collection techniques used are observation, documentation, and tests. The analysis used is validy test, reliability test, normality test, homogeneity test, product moment correlation test, significance test and determination test. The research location is at junior high school 12 in Palirangan.Based on the results of calculating data values in hypothesis testing, the researcher used a product moment correlation test on 25 respondents which a significant influence method on student learning outcomes in Fiqh subject with r???????? = 0,875. Meanwhile, for significance test, the result obtained was t = 8,838 at the 5% significance level, which was 2,068. From this discussion, it shows that there is a positive and significant influence between the game based learning(GBL) method on student learning outcomes in Fiqh subjects.